Automatic feeding mechanism of a vegetable transplanter - Kumar, Prasanna; Raheman, H. (International Journal of Agricultural and Biological Engineering, 2012)
Prasanna Kumar G. V.1*, H. Raheman2 (1. Department of Agricultural Engineering, Triguna Sen School of Technology, Assam University, Silchar 788011, Assam, India; 2. Department of Agricultural and Food Engineering, Indian Institute of Technology, Kharagpur 721302, West Bengal, India) Abstract: An automatic feeding mechanism consisting of a timing shaft, an actuating device and a clutch for feeding paper pot seedlings from a horizontal slat type chain conveyor to a horizontal pusher type chain conveyor of a vegetable transplanter, was developed. The slat type chain conveyor carried the pot seedlings in upright orientation in the form of a rectangular array with each linear array of pot seedlings on a slat. The pusher type chain conveyor received a linear array of pot seedlings and delivered them to the seedling drop tube. Feeding of each linear array of pot seedlings to the pusher type conveyor at appropriate times was done using an automatic feeding mechanism. The laboratory evaluation indicated that the feeding rate of 33 to 50 pot seedlings per minute can be achieved with single set of conveyors. The feeding mechanism also worked effectively under actual field conditions with 98% to 99% of all the pot seedlings, which were properly separated and fed for planting when the forward speed of the vegetable transplanter was 0.9 km/h. The feeding mechanism has the general application of singulating rectangular array of items on the slat type chain conveyor in any industry and machine in motion on a level surface. Keywords: automatic feeding mechanism, chain conveyor, feed index, singulation, vegetable transplanter DOI: 10.3965/j.ijabe.20120502.003 Citation: Prasanna Kumar G V, Raheman H. Automatic feeding mechanism of a vegetable transplanter. Int J Agric & Biol Eng, 2012; 5(2): 20